Energy-saving and heat-insulating coating for industrial furnace
By using spinel-silicate multiphase composite system infrared radiation ceramic powder and composite silicate multifunctional powder, energy-saving insulation coatings with low thermal conductivity, good bonding strength and high compressive strength are prepared. , solves the problems of high thermal conductivity, insufficient bonding strength and poor high temperature stability of existing coatings, and achieves more efficient kiln insulation and longer service life.
Patent Information
- Application Number
- CN202411607386.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
AI Technical Summary
The existing energy-saving insulation coatings used in industrial kilns have high thermal conductivity, limited insulation effect, insufficient bonding strength, easy to fall off, poor high temperature stability, short service life, and require frequent maintenance, which increases production costs.
Using spinel-silicate multiphase composite system infrared radiation ceramic powder and composite silicate multifunctional powder, combined with bentonite, asbestos lint, ceramic fibers, rare earth oxides and other raw materials, through reasonable proportioning and interact to prepare energy-saving thermal insulation coatings with low thermal conductivity, good bonding strength and high compressive strength.
It significantly reduces the thermal conductivity of the paint, improves the insulation effect of the kiln, extends the service life of the kiln, reduces energy consumption and production costs, and enhances the high-temperature stability and environmental protection performance of the paint.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thermal insulation coatings, and more specifically, to an energy-saving thermal insulation coating for industrial furnaces. Background Art
[0002] During the operation of industrial kilns, energy consumption is huge, and improving the energy utilization efficiency of kilns has become an urgent problem to be solved.
[0003] Existing energy-saving and thermal insulation coatings for industrial kilns, such as coatings mixed with expanded perlite, bentonite, asbestos wool, ceramic fiber, water, polyacrylamide, binders, etc., have certain thermal insulation properties, but still have many shortcomings. For example, its thermal conductivity is relatively high, resulting in limited thermal insulation effect; insufficient bonding strength, easy to cause coating shedding; poor high temperature stability, short service life in the high temperature environment of the kiln, frequent maintenance is required, and increased production costs.
[0004] Therefore, an energy-saving and heat-insulating coating for industrial kilns is now proposed. Summary of the invention
[0005] In order to overcome the above-mentioned defects of the prior art, the present invention provides an energy-saving and thermal insulation coating for industrial kilns to solve the problems raised in the above-mentioned background technology.
[0006] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: an energy-saving and thermal insulation coating for industrial kilns, composed of the following raw materials in parts by weight: 10-30 parts of spinel-silicate multiphase composite system infrared radiation ceramic powder, 30-70 parts of effective ingredients in composite silicate multifunctional powder, 5-10 parts of bentonite, 3-8 parts of asbestos wool, 5-10 parts of ceramic fiber, 15-30 parts of water, 0.5-2 parts of polyacrylamide, 5-10 parts of binder, 1-5 parts of glass powder, and 0.5-3 parts of rare earth oxide.
[0007] Preferably, the effective ingredients in the composite silicate multifunctional powder include aluminum silicate fiber wool, expanded perlite, hydraulic cementitious material, modified sepiolite, waterproof enhancer, and viscosity enhancer.
[0008] Preferably, the rare earth oxide is cerium oxide, lanthanum oxide or a mixture of the two.
[0009] A method for preparing an energy-saving and heat-insulating coating for an industrial kiln comprises the following steps:
[0010] Weigh each raw material according to the formula amount for later use;
[0011] The spinel-silicate multiphase composite system infrared radiation ceramic powder, expanded perlite, bentonite, asbestos wool, ceramic fiber and rare earth oxide are uniformly mixed to obtain a mixed powder;
[0012] The effective components in the composite silicate multifunctional powder are made into slurry according to the corresponding preparation method;
[0013] Add polyacrylamide into water to dissolve it, then add a binder and stir evenly to obtain a mixed solution;
[0014] Add the mixed liquid to the mixed powder, stir evenly, then add the glass powder, continue stirring until evenly mixed, to obtain a coating slurry;
[0015] The coating slurry is ground to make its particle size reach the required range to obtain energy-saving thermal insulation coating.
[0016] Preferably, the preparation method of the active ingredient in the composite silicate multifunctional powder is:
[0017] Preparation of aluminum silicate fiber cotton slurry: Mix aluminum silicate fiber cotton with fiber material dispersant and appropriate amount of water, stir and disperse evenly;
[0018] Preparation of hydraulic cementitious materials: Mix 325# Portland cement and natural zeolite powder evenly, or use 425# Portland cement or 525# high alumina cement;
[0019] Preparation of modified sepiolite slurry: Mix fibrous sepiolite with cationic modifier octadecyltrimethylammonium chloride (bromide) and appropriate amount of water to adsorb and modify the sepiolite;
[0020] Preparation of waterproof enhancer: 1799 polyvinyl alcohol, anti-skinning agent ammonium chloride, modifier borax, water repellent stearic acid, emulsifier sodium carbonate, catalyst industrial light rare earth cerium oxide, and water are processed in a certain proportion and process to make a milky white solution;
[0021] Preparation of thickener slurry: Mix and dissolve water glass, urea, carboxymethyl cellulose, polyacrylamide and appropriate amount of water.
[0022] Preferably, the coating slurry is ground to a particle size of less than 74 μm.
[0023] Preferably, the application of the coating in industrial kilns can reduce the surface temperature of the kiln, improve energy efficiency, and extend the service life of the kiln.
[0024] Preferably, the glass powder is made of SiO 2 65%、Al 2 O 3 15%, CaO5%, BaO3%, MgO8%, TiO 2 2%, ZnO2%.
[0025] Preferably, the method for preparing the spinel-silicate multiphase composite infrared radiation ceramic powder comprises: mixing component A forming a spinel solid solution, component B forming a silicate mineral and component C as a promoter in a mass ratio of 100%: 20-300%: 0-15%, wherein component A comprises Fe 2 O 3 、MnO 2 ,CuO,Co 2 O 3 、Mo 2 O 3 、NiO、V 2 O 5 , WO 3 , component B includes Al 2 O 3 、SiO 2 , MgO, BaO, CaO, TiO 2 , component C includes glass powder and B 2 O 3 ; The ingredients are ball-milled, mixed, dried and pressed into a block body; the block body is heated and kept at 800-980°C for 1-6 hours to form a spinel solid solution, and then heated and kept at 1100-1300°C for 2-8 hours to form a silicate mineral, so that the spinel solid solution and the silicate mineral are multi-phase composited to form a black sintered body, which is then crushed, pulverized and sieved to obtain.
[0026] Preferably, the specific content of the A component, the B component and the C component is 20% Fe 2 O 3 、12%MnO 2 , 2.4%CuO, 2.4%Mo 2 O 3 , 2%V 2 O 5 、1.2%WO 3 、20%Al 2 O 3 、25.1%SiO 2 , 10% MgO, 1.5% BaO, 1.4% CaO, 1% glass powder and 1% B 2 O 3 ; or 11% MnO 2 、10%Co 2 O 3 、3%NiO、5%WO 3 、50%Al 2 O 3 , 9%SiO 2 、6%TiO 2 , 3% CaO and 3% glass powder; or 60% MnO 2, 4%CuO, 2%Mo 2 O 3 、3%V 2 O 5 、6%NiO、11%Al 2 O 3 、5%SiO 2 、3%TiO 2 , 2%BaO, 2% glass powder and 2%B 2 O 3 ; or 11% Fe 2 O 3 、30%MnO 2 、3%CuO、2%Mo 2 O 3 , 2%V 2 O 5 、1%WO 3 、33%Al 2 O 3 、14%SiO 2 , 3% CaO and 1% glass powder.
[0027] Technical effects and advantages of the present invention:
[0028] 1. By adding the effective ingredients of the spinel-silicate multiphase composite system infrared radiation ceramic powder and the composite silicate multifunctional powder, and utilizing their respective low thermal conductivity characteristics and synergistic effects, the thermal conductivity of the coating is significantly reduced, and the thermal conductivity can reach ≤0.15W / (m·K). Compared with traditional coatings, it greatly reduces the conduction of heat, effectively prevents the heat inside the kiln from dissipating to the outside, improves the thermal insulation effect of the kiln, and reduces energy consumption.
[0029] 2. The infrared radiation ceramic powder of the spinel-silicate multiphase composite system has good infrared radiation performance, which can reflect and absorb the heat radiation in the kiln to a certain extent, reduce the transmission of heat radiation to the outside through the coating layer, and further enhance the thermal insulation capacity of the coating.
[0030] 3. Through the effective ingredients in the composite silicate multifunctional powder (such as aluminum silicate fiber cotton, modified sepiolite, waterproof enhancer, tackifier, etc.) and other raw materials, the bonding strength between the coating and the industrial kiln substrate is significantly improved, and the bonding strength is ≥200KPa, so that the coating can be firmly attached to the kiln surface and is not prone to falling off or cracking, thereby ensuring the stability of the coating in long-term high-temperature environments.
[0031] 4. Through the reasonable proportion and interaction between the raw materials, the coating has a high compressive strength, which is ≥18MPa. This enables the coating to withstand the pressure, mechanical vibration and material impact generated during the operation of the kiln, and is not prone to deformation and damage, effectively protecting the kiln substrate and extending the service life of the kiln.
[0032] 5. The addition of rare earth oxides (such as cerium oxide, lanthanum oxide, etc.) effectively improves the stability of the coating at high temperatures. In the high temperature range of 1000-1500°C, the coating can maintain good physical and chemical properties and will not soften, melt, decompose, etc. due to high temperatures. This ensures the long-term stable use of the coating in the high temperature environment of industrial kilns, reduces frequent maintenance and replacement due to coating failure, and reduces production costs.
[0033] 6. Under high temperature conditions, the various components in the coating work together to inhibit the thermal expansion, oxidation and other degradation processes of the material, maintain the integrity of the coating structure and the stability of its performance, thereby continuing to play its role in energy saving, heat preservation and kiln protection.
[0034] 7. In the formula design, the use of substances such as asbestos wool that may be harmful to the human body and the environment is minimized. At the same time, environmentally friendly raw materials and preparation processes are used to reduce the risk of environmental pollution during the production and use of the coating, meet environmental protection requirements, and are beneficial to the health of operators and environmental protection.
[0035] 8. Some raw materials in the coating (such as aluminum silicate fiber cotton, etc.) have good fire resistance, which makes the coating as a whole have a certain fire resistance. During the operation of the kiln, even if an emergency occurs, it can prevent the spread of flames to a certain extent, thereby improving the safety of industrial kilns.
[0036] 9. The excellent thermal insulation performance greatly reduces the heat loss of the kiln, reduces fuel consumption, improves energy utilization efficiency, reduces the energy cost of the enterprise, and also reduces the environmental pollution caused by energy consumption.
[0037] In summary, the coating of the present invention has good bonding strength, mechanical properties and high-temperature stability, which can effectively protect the kiln substrate, reduce kiln corrosion, wear and other problems caused by coating damage, extend the maintenance cycle and overall service life of the kiln, reduce equipment renewal costs, and improve the production efficiency of the enterprise. DETAILED DESCRIPTION
[0038] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0039] Example 1
[0040] Raw material preparation
[0041] Spinel-silicate multiphase composite system infrared radiation ceramic powder: 20 parts (prepared according to the following method: take 20% Fe 2 O 3 、12%MnO 2 , 2.4%CuO, 2.4%Mo 2 O 3 , 2%V 2 O 5 、1.2%WO 3 、20%Al 2 O 3 、25.1%SiO 2 , 10% MgO, 1.5% BaO, 1.4% CaO, 1% glass powder and 1% B 2 O 3 The glass powder is made of SiO 2 65%、Al 2 O 3 15%, CaO5%, BaO3%, MgO8%, TiO 2 2%, ZnO2%. The ingredients are ball-milled, mixed, dried, and pressed into a block body, first kept at 950°C for 4 hours to form a spinel solid solution, then heated to 1200°C for 2 hours to form a silicate mineral, and a black sintered body is obtained after multi-phase composite, which is crushed, pulverized and passed through a 320-mesh sieve)
[0042] The effective ingredients in the composite silicate multifunctional powder are: 50 parts (including 6.75 parts of aluminum silicate fiber cotton, 71.25 parts of expanded perlite, 91.08 parts of hydraulic cementitious material (mixed by 5.41-176.10 parts of 325# silicate cement and 2.72-31.07 parts of natural zeolite powder with a particle size of >200 mesh), 29.64 parts of modified sepiolite (composed of fibrous sepiolite, 0.02 parts of cationic modifier octadecyltrimethylammonium chloride (bromide) and appropriate amount of water), 150.00 parts of waterproof enhancer, and 4.58 parts of tackifier)
[0043] Bentonite: 8 parts
[0044] Asbestos wool: 5 parts
[0045] Ceramic fiber: 8 parts
[0046] Water: 20 parts
[0047] Polyacrylamide: 1 part
[0048] Binder: 8 parts
[0049] Glass powder: 3 parts
[0050] Rare earth oxide (cerium oxide): 1 part
[0051] Preparation process
[0052] The spinel-silicate multiphase composite system infrared radiation ceramic powder, 15 parts of expanded perlite, bentonite, asbestos wool, ceramic fiber and rare earth oxide are uniformly mixed to obtain a mixed powder.
[0053] Prepare each slurry according to the preparation method of the effective ingredients in the composite silicate multifunctional powder:
[0054] Aluminum silicate fiber cotton slurry: Mix aluminum silicate fiber cotton with 0.2 parts of soap powder (fiber material dispersant) and appropriate amount of water, and stir to disperse evenly.
[0055] Hydraulic cementitious material: Mix 5.41-176.10 parts of 325# Portland cement and 2.72-31.07 parts of natural zeolite powder with a particle size of >200 mesh.
[0056] Modified sepiolite slurry: Mix fibrous sepiolite with 0.02 parts of cationic modifier octadecyltrimethylammonium chloride (bromide) and an appropriate amount of water to allow the sepiolite to undergo cation adsorption and modification.
[0057] Waterproof enhancer: 0.75-8.00 parts of 1799 type polyvinyl alcohol, 0.01-0.16 parts of anti-skinning agent ammonium chloride, 0.00008-0.0008 parts of modifier borax, 1.50-16.00 parts of water repellent stearic acid, 0.05-0.48 parts of emulsifier sodium carbonate, 0.01-0.10 parts of catalyst industrial light rare earth cerium oxide, and 27.69-295.38 parts of clean water are processed according to a certain proportion and process to make a milky white solution.
[0058] Thickener slurry: 0.75-8.00 parts of water glass, 0.02-0.16 parts of urea, 0.02-0.64 parts of carboxymethyl cellulose, 0.09-0.96 parts of polyacrylamide and appropriate amount of water are mixed and dissolved.
[0059] Add polyacrylamide into water and dissolve it, then add a binder and stir evenly to obtain a mixed solution.
[0060] The mixed liquid is added to the mixed powder, stirred evenly, and then the glass powder is added, and the stirring is continued until uniform to obtain a coating slurry.
[0061] The coating slurry is ground to a particle size of less than 74 μm to obtain an energy-saving thermal insulation coating.
[0062] Performance Testing
[0063] After testing, the coating has a thermal conductivity of 0.12W / (m·K), a bonding strength of 220KPa, a compressive strength of 20MPa, a linear shrinkage of 6%, and can be used stably at 1000-1500℃, with good energy-saving and thermal insulation effects and high-temperature stability.
[0064] Example 2
[0065] Raw material preparation
[0066] Spinel-silicate multiphase composite system infrared radiation ceramic powder: 15 parts (prepared according to the following method: take 11% MnO 2 、10%Co 2 O 3 、3%NiO、5%WO 3 、50%Al 2 O 3 , 9%SiO 2 、6%TiO 2 , 3% CaO and 3% glass powder are prepared, and the composition of the glass powder is the same as that of Example 1. The ingredients are ball-milled, mixed, dried, and pressed into a block body, first heated at 800°C for 6 hours to form a spinel solid solution, then heated to 1300°C for 6 hours to form a silicate mineral, and a black sintered body is obtained after multi-phase composite, which is crushed, pulverized and passed through a 200-mesh sieve to prepare)
[0067] Active ingredients in composite silicate multifunctional powder: 60 parts (8.10 parts of aluminum silicate fiber cotton, 85.50 parts of expanded perlite, 109.30 parts of hydraulic cementitious material (425# silicate cement), 35.57 parts of modified sepiolite (composed of fibrous sepiolite, 0.03 parts of cationic modifier octadecyltrimethylammonium chloride (bromide) and appropriate amount of water), 180.00 parts of waterproof enhancer, 5.49 parts of tackifier)
[0068] Bentonite: 6 parts
[0069] Asbestos wool: 6 parts
[0070] Ceramic fiber: 6 parts
[0071] Water: 25 parts
[0072] Polyacrylamide: 1.5 parts
[0073] Binder: 6 parts
[0074] Glass powder: 2 parts
[0075] Rare earth oxide (lanthanum oxide): 2 parts
[0076] Preparation process
[0077] The same preparation process as in Example 1 is used to mix the raw materials, prepare the slurry, stir and grind them according to the corresponding steps to obtain the energy-saving and thermal insulation coating.
[0078] Performance Testing
[0079] The test results show that the thermal conductivity of the coating is 0.13W / (m·K), the bonding strength is 230KPa, the compressive strength is 22MPa, the linear shrinkage is 5%, and the performance is stable in a high temperature environment of 1000-1500℃, which can effectively improve the energy saving effect and service life of industrial kilns.
[0080] Example 3
[0081] Raw material preparation
[0082] Spinel-silicate multiphase composite system infrared radiation ceramic powder: 25 parts (prepared according to the following method: take 60% MnO 2 , 4%CuO, 2%Mo 2 O 3 、3%V 2 O 5 、6%NiO、11%Al 2 O 3 、5%SiO 2 、3%TiO 2 , 2%BaO, 2% glass powder and 2%B 2 O 3 The ingredients are prepared, and the glass powder composition is the same as that of Example 1. The ingredients are ball-milled, mixed, dried, and pressed into a block body, first kept at 850°C for 5 hours to form a spinel solid solution, then heated to 1100°C for 8 hours to form a silicate mineral, and a black sintered body is obtained after multi-phase composite, which is crushed, pulverized, and passed through a 230-mesh sieve to prepare the product.
[0083] The effective ingredients in the composite silicate multifunctional powder are: 40 parts (including 4.05 parts of aluminum silicate fiber cotton, 42.75 parts of expanded perlite, 54.65 parts of hydraulic cementitious material (mixed by 5.41-176.10 parts of 325# silicate cement and 2.72-31.07 parts of natural zeolite powder with a particle size of >200 mesh), 17.78 parts of modified sepiolite (composed of fibrous sepiolite, 0.02 parts of cationic modifier octadecyltrimethylammonium chloride (bromide) and appropriate amount of water), 90.00 parts of waterproof enhancer, and 2.75 parts of tackifier)
[0084] Bentonite: 7 parts
[0085] Asbestos wool: 4 parts
[0086] Ceramic fiber: 7 parts
[0087] Water: 18 parts
[0088] Polyacrylamide: 0.8 parts
[0089] Binder: 7 parts
[0090] Glass powder: 4 parts
[0091] Rare earth oxide (cerium oxide and lanthanum oxide mixed in a ratio of 1:1): 1.5 parts
[0092] Preparation process
[0093] The preparation steps of Example 1 were repeated to prepare an energy-saving thermal insulation coating.
[0094] Performance Testing
[0095] The coating has a thermal conductivity of 0.14W / (m·K), a bonding strength of 210KPa, a compressive strength of 19MPa, a linear shrinkage of 7%, and maintains good performance at 1000-1500℃, making it suitable for the energy-saving and thermal insulation needs of industrial kilns.
[0096] Example 4
[0097] Raw material preparation
[0098] Spinel-silicate multiphase composite system infrared radiation ceramic powder: 30 parts (prepared according to the following method: take 11% Fe 2 O 3 、30%MnO 2 、3%CuO、2%Mo 2 O 3 , 2%V 2 O 5 、1%WO 3 、33%Al 2 O 3 、14%SiO 2 , 3% CaO and 1% glass powder are prepared, and the composition of the glass powder is the same as that of Example 1. The ingredients are ball-milled, mixed, dried, and pressed into a block body, first heated at 900°C for 2 hours to form a spinel solid solution, then heated to 1150°C for 6 hours to form a silicate mineral, and a black sintered body is obtained after multi-phase composite, which is crushed, pulverized and passed through a 400-mesh sieve to prepare)
[0099] The effective ingredients in the composite silicate multifunctional powder are: 35 parts (including 9.45 parts of aluminum silicate fiber cotton, 99.75 parts of expanded perlite, 127.51 parts of hydraulic cementitious material (mixed by 5.41-176.10 parts of 325# silicate cement and 2.72-31.07 parts of natural zeolite powder with a particle size of >200 mesh), 41.50 parts of modified sepiolite (composed of fibrous sepiolite, 0.03 parts of cationic modifier octadecyltrimethylammonium chloride (bromide) and appropriate amount of water), 210.00 parts of waterproof enhancer, and 6.41 parts of tackifier)
[0100] Bentonite: 10 parts
[0101] Asbestos wool: 3 parts
[0102] Ceramic fiber: 10 parts
[0103] Water: 30 parts
[0104] Polyacrylamide: 2 parts
[0105] Binder: 10 parts
[0106] Glass powder: 5 parts
[0107] Rare earth oxide (cerium oxide): 3 parts
[0108] Preparation process
[0109] According to the preparation process of Example 1, the raw materials are mixed and processed to obtain the energy-saving and thermal insulation coating.
[0110] Performance Testing
[0111] After testing, the coating has a thermal conductivity of 0.11W / (m·K), a bonding strength of 250KPa, a compressive strength of 25MPa, and a linear shrinkage of 4%. It exhibits excellent stability and energy-saving and thermal insulation properties at high temperatures of 1000-1500℃, and can effectively improve the operating efficiency and life of industrial kilns.
[0112] In summary, the comprehensive properties of the coatings prepared in Examples 1-4 are:
[0113] Thermal conductivity: ≤0.15W / (m·K), significantly lower than existing coatings, effectively reducing heat loss.
[0114] Bonding strength: ≥200KPa, strong bonding, not easy to fall off.
[0115] Compressive strength: ≥18MPa, able to withstand the pressure during kiln operation.
[0116] Linear shrinkage: ≤8%, small shrinkage deformation at high temperature.
[0117] High temperature stability: It can be used for a long time at 1000-1500℃ and adapt to the high temperature environment of industrial kilns.
[0118] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An energy-saving and heat-insulating coating for industrial kilns, characterized in that: The invention is composed of the following raw materials in parts by weight: 10-30 parts of spinel-silicate multiphase composite infrared radiation ceramic powder, 30-70 parts of effective ingredients in composite silicate multifunctional powder, 5-10 parts of bentonite, 3-8 parts of asbestos wool, 5-10 parts of ceramic fiber, 15-30 parts of water, 0.5-2 parts of polyacrylamide, 5-10 parts of binder, 1-5 parts of glass powder and 0.5-3 parts of rare earth oxide.
2. The energy-saving thermal insulation coating according to claim 1, characterized in that: The effective ingredients in the composite silicate multifunctional powder include aluminum silicate fiber cotton, expanded perlite, hydraulic gelling material, modified sepiolite, waterproof enhancer and viscosity enhancer.
3. The energy-saving thermal insulation coating according to claim 1, characterized in that: The rare earth oxide is cerium oxide, lanthanum oxide or a mixture of the two.
4. A method for preparing an energy-saving and heat-insulating coating for an industrial kiln, characterized in that: The following steps are involved: Weigh each raw material according to the formula amount for later use; The spinel-silicate multiphase composite system infrared radiation ceramic powder, expanded perlite, bentonite, asbestos wool, ceramic fiber and rare earth oxide are uniformly mixed to obtain a mixed powder; The effective components in the composite silicate multifunctional powder are made into slurry according to the corresponding preparation method; Add polyacrylamide into water to dissolve it, then add a binder and stir evenly to obtain a mixed solution; Add the mixed liquid to the mixed powder, stir evenly, then add the glass powder, continue stirring until evenly mixed, to obtain a coating slurry; The coating slurry is ground to make its particle size reach the required range to obtain energy-saving thermal insulation coating.
5. The preparation method according to claim 4, characterized in that: The preparation method of the active ingredient in the composite silicate multifunctional powder is as follows: Preparation of aluminum silicate fiber cotton slurry: Mix aluminum silicate fiber cotton with fiber material dispersant and appropriate amount of water, stir and disperse evenly; Preparation of hydraulic cementitious materials: Mix 325# Portland cement and natural zeolite powder evenly, or use 425# Portland cement or 525# high alumina cement; Preparation of modified sepiolite slurry: Mix fibrous sepiolite with cationic modifier octadecyltrimethylammonium chloride (bromide) and appropriate amount of water to adsorb and modify the sepiolite; Preparation of waterproof enhancer: 1799 polyvinyl alcohol, anti-skinning agent ammonium chloride, modifier borax, water repellent stearic acid, emulsifier sodium carbonate, catalyst industrial light rare earth cerium oxide, and water are processed in a certain proportion and process to make a milky white solution; Preparation of thickener slurry: Mix and dissolve water glass, urea, carboxymethyl cellulose, polyacrylamide and appropriate amount of water.
6. The preparation method according to claim 4, characterized in that: The coating slurry was ground to a particle size of less than 74 μm.
7. The energy-saving thermal insulation coating according to claim 1, characterized in that: The application of this coating in industrial kilns can reduce the surface temperature of the kiln, improve energy utilization efficiency and extend the service life of the kiln.
8. The energy-saving thermal insulation coating according to claim 1, characterized in that: The glass powder consists of SiO2 65%, Al2O3 15%, CaO 5%, BaO 3%, MgO 8%, TiO2 2%, and ZnO 2%.
9. The energy-saving thermal insulation coating according to claim 1, characterized in that: The preparation method of the spinel-silicate multiphase composite system infrared radiation ceramic powder comprises: mixing component A forming a spinel type solid solution, component B forming a silicate mineral and component C as a promoter in a mass ratio of 100%:20-300%:0-15%, wherein component A comprises Fe2O3, MnO2, CuO, Co2O3, Mo2O3, NiO, V2O5 and WO3, component B comprises Al2O3, SiO2, MgO, BaO, CaO and TiO2, and component C comprises glass powder and B2O3; ball milling, mixing, drying and pressing the ingredients into a block body; heating and keeping the block body at 800-980°C for 1-6 hours to form a spinel type solid solution, then heating and keeping the block body at 1100-1300°C for 2-8 hours to form a silicate mineral, so that the spinel type solid solution and the silicate mineral are multiphase composited to form a black sintered body, and then crushing, pulverizing and sieving to obtain the obtained product.
10. The energy-saving thermal insulation coating according to claim 9, characterized in that: The specific contents of the A component, the B component and the C component are 20% Fe2O3, 12% MnO2, 2.4% CuO, 2.4% Mo2O3, 2% V2O5, 1.2% WO3, 20% Al2O3, 25.1% SiO2, 10% MgO, 1.5% BaO, 1.4% CaO, 1% glass powder and 1% B2O3; or 11% MnO2, 10% Co2O3, 3% NiO, 5% WO3, 50% Al2O3, 9% SiO2, 6% TiO2, 3% CaO and 3% glass powder; or 60% MnO2, 4% CuO, 2% Mo2O3, 3% V2O5, 6% NiO, 11% Al2O3, 5% SiO2, 3% TiO2, 2% BaO, 2% glass powder and 2% B2O3; or 11% Fe2O3, 30% MnO2, 3% CuO, 2% Mo2O3, 2% V2O5, 1% WO3, 33% Al2O3, 14% SiO2, 3% CaO and 1% glass powder.
Citation Information
Patent Citations
Multiphase composite system infrared radiation ceramic powder and preparation method thereof
CN102219496A
Preparation method of infrared radiation ceramic powder in spinel-silicate multi-phase composite system
CN102701746A